2021
DOI: 10.1152/ajpheart.00737.2020
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ATGL in adipose tissue ameliorates isoproterenol-induced cardiac remodeling by reducing adipose tissue inflammation

Abstract: Following cardiac injury, increased adrenergic drive plays an important role in compensating for reduced cardiac function. However, chronic excess adrenergic stimulation can be detrimental to cardiac pathophysiology and can also affect other organs including adipose tissue leading to increased lipolysis. Interestingly, inhibition of adipose triglyceride lipase (ATGL), the rate-limiting enzyme in lipolysis, in adipocytes ameliorates cardiac dysfunction in a heart failure model. Thus, we investigated whether inh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 61 publications
0
17
0
Order By: Relevance
“… 58 A very recent study suggested the role of galectin-3 in Atglistatin-mediated cardioprotection. 27 This protein belongs to the family of β-galactoside-binding proteins and is known to promote inflammation and fibrosis in the heart and other organs. 59 Notably, ATGL inactivation reduced galectin-3 levels in vivo and ameliorated isoproterenol-induced galectin-3 secretion in adipose tissue organ cultures.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 58 A very recent study suggested the role of galectin-3 in Atglistatin-mediated cardioprotection. 27 This protein belongs to the family of β-galactoside-binding proteins and is known to promote inflammation and fibrosis in the heart and other organs. 59 Notably, ATGL inactivation reduced galectin-3 levels in vivo and ameliorated isoproterenol-induced galectin-3 secretion in adipose tissue organ cultures.…”
Section: Discussionmentioning
confidence: 99%
“…The authors concluded that reduced galectin-3 secretion in response to ATGL inhibition contributes to the protective effects of Ai. 27 …”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, pharmacological or genetic inhibition of ATGL in adipocytes ameliorates Iso-induced cardiac inflammation, hypertrophy and fibrosis likely by reducing adipose tissue inflammation and reducing galectin-3 secretion from adipose tissue [ 134 ]. Of note our results indicate that Pnpla2 induction in cardiac Iso ECH macrophages is associated with upregulation of Lgals3 (coding for Galectin-3).…”
Section: Discussionmentioning
confidence: 99%
“…ATGL plays a critical role in modulating lipid metabolism and cardiac function (Foryst-Ludwig et al 2015;Salatzki et al 2018). Ablation of ATGL in adipose tissues or inhibition of ATGL by Atglistatin (predominantly targeting ATGL in adipose tissue) was shown to prevent cardiac damage and dysfunction by reducing galectin-3 or fatty acid secretion from adipocyte tissues (Takahara et al 2021;Thiele et al 2021), implying that adipocytic ATGL is involved in cardiac remodeling and dysfunctions. However, several studies have revealed that ATGL in cardiomyocytes directly regulates cardiac metabolism and mitochondrial substrate oxidation through different mechanisms (Gao et al 2015, Haemmerle et al 2011Kienesberger et al 2012).…”
Section: Discussionmentioning
confidence: 99%